Recent Progress in High‐efficiency Planar‐structure Perovskite Solar Cells - Zhao, Yang; Ye, Qiufeng; Chu, Zema; Gao, Feng; Zhang, Xingwang; You, Jingbi (Energy & environmental materials (Hoboken, N.J.), 2019)
Lead halide perovskite owns charge diffusion length in micrometer range, which makes the planar‐structure solar cells possible. The simple and low‐temperature process of planar devices makes it very promising. The power conversion efficiency of planar perovskite solar cells has increased from 1.8% to 23.7% in past several years, which can compete with the mesoporous structure counterpart. In this minireview, recent progress in high‐efficiency planar perovskite solar cells will be summarized. Efficiency progresses in planar perovskite solar cells